Integration of Islamic Values on Social Studies Education Madrasah Tsanawiyah Al Musaddadiyah Garut - Puad, Dede (Universitas Pendidikan Indonesia (UPI), 2022)
Abstract. The purpose of this study was to determine the integration of Islamic values in learning at MTs Al-Musaddadiyah Garut. This type of research uses qualitative methods. While the data collection instruments in the form of observations, interviews, and documentation studies. The results showed that the integration of Islamic values in learning at MTs Al-Musaddadiyah Garut is to foster and develop Islamic values through the provision of knowledge development, example, practice, habituation, and the experience of students who are integrated in learning activities. The integration of coherent ancient values in the KBM process begins with the opening of the process and closing. Learning begins with a prayer asking for useful knowledge, the material KBM process is always integrated with the giver of knowledge, Allah swt for the blessings and benefits of knowledge itself for self, others and environment, the closing of the KBM reflects the benefits of knowledge to be practiced in everyday life.